2014
DOI: 10.1057/jibs.2013.68
|View full text |Cite
|
Sign up to set email alerts
|

International experience and FDI location choices of Chinese firms: The moderating effects of home country government support and host country institutions

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. sub-sample analyses we identify differences between entering developed and developing host countries in terms of the impact of home country government support and quality of host country institutions. Our findings help explain the puzzle concerning why EE firms have rapidly internationalized in a short period of time and do not follow the pattern predicted by classical IB theories. In comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
373
1
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 414 publications
(394 citation statements)
references
References 90 publications
9
373
1
11
Order By: Relevance
“…This strategy, however, is associated with several difficult challenges because of the heightened international exposure, competition and additional environmental risks present in foreign host countries (Elango, 2009;Lu, Liu, Wright & Filatotchev, 2014;Jimenes & Delgado-Garcia, 2012). Environmental risks in host countries, such as political and industry risk, represent uncertainties and potential threats for multinational enterprises (MNEs) (Cuypers & Martin, 2010;Henisz, 2000Henisz, , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy, however, is associated with several difficult challenges because of the heightened international exposure, competition and additional environmental risks present in foreign host countries (Elango, 2009;Lu, Liu, Wright & Filatotchev, 2014;Jimenes & Delgado-Garcia, 2012). Environmental risks in host countries, such as political and industry risk, represent uncertainties and potential threats for multinational enterprises (MNEs) (Cuypers & Martin, 2010;Henisz, 2000Henisz, , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…The findings from existing studies have enhanced our understanding of the importance of expatriates in MNEs' overseas operations. However, these studies have paid little attention to the impact of expatriates on subsidiary autonomy (Aharoni, Tihanyi, & Connelly, 2011) and how EEMNEs respond to external uncertainty by adjusting their internal management strategies (Davis & Cobb, 2010), such as the levels of localisation (Liu, et al, 2016;Lu, et al, 2014;Yildiz & Fey, 2012) and parental support (Feinberg & Gupta, 2009;Luo, 2003). The resource dependence theory (RDT) has been increasingly influential as a theoretical basis for international business research.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…3 Despite attempts by the Chinese government to reduce the direct engagement of government agencies in economic activity and a declining trend in such activity, government agencies continue to engage directly in economic activity with local and foreign businesses in the PRC (Cui & Jiang, 2012, Lu, Liu, Wright, & Filatotchev, 2014 4 To avoid small numbers of observations in individual industries we grouped industries as shown in Table 1. We also ran our models by using alternative industry groupings and confirmed that our results remain stable across different classifications.…”
Section: Endnotesmentioning
confidence: 99%